Effect of Shockwave on Postnatal Coccydynia: A Randomized Controlled Clinical Trial - Dina S. Mohammed , Soheir M. ElKosery , Nabil M. Fekry , Mohamed Salah El Sayed , Afaf M. Botla (Cuestiones de Fisioterapia, 2025)
Background: One of the major problems affecting postpartum women is coccydynia, which makes it difficult for them to carry out everyday tasks, and even leads to an inability to work. Objective: To ascertain how shockwave therapy affects postpartum women's coccydynia. Material and Methods: Forty-six postnatal females who had coccydynia for at least six weeks following delivery (N = 46), aged between 25 and 35 years, were recruited from Al-Agoza Police Hospital, Giza, Egypt. The females were split randomly into a study group (A) (n = 23) and a control group (B) (n = 23). The study group participants were treated by shockwave therapy (SWT) (1 session weekly for 4 weeks), medical treatment in the form of Ibuprofen (400 mg) twice daily for 4 weeks, and behavioral therapy advice. The control group participants received the same medical treatment plus behavioral therapy advice only. Pain intensity, pain pressure threshold (PPT), functional disability, and lumbar mobility were measured for the two groups by using the visual analogue scale (VAS), pressure algometer, Oswestry disability index (ODI), and modified-modified Schober Test (MMST), respectively, before and after 4 weeks ofthe treatment program. Results: Following treatment, both groups (A and B) showed a statistically significantreduction in VAS and ODI, as well as a significant increase in PPT and MMST in flexion and extension as compared to baseline. Comparing between groups revealed a statistically significant reduction in VAS (p = 0.001), ODI (p = 0.006), and a significant increase in PPT (p = 0.001) and MMST in flexion (p = 0.001) and extension (p = 0.005) in favor of group A.Conclusion: These findings suggest shockwave therapy as an efficient, conservative therapeutic approach for treating coccydynia in postnatal women.